(untitled) (Research, Society and Development, 2022)
Non-Timber Forest Products (NTFPs) are those of plant origin, in the North region of Brazil the Brazil nut (Bertholletia excelsa H.B.K) deserves to be highlighted, since it is a source of income for countless communities in the Amazon, in addition to one of the main NTFPs exported by the states of this region. However, Brazil nut extractivism faces challenges such as environmental issues, growth of the agricultural frontier and cities, climate issues, in addition to an extraction model that employs a low technological level and demands a large amount of labor. This study aims to analyze the production of Brazil nuts regarding the behavior of the quantity produced (1968-2020) and price for the period 1990-2020 and exports and imports, for the period 1997-2021 and related aspects. nut consumption, so that it is possible to understand the market and production of this important NTFP for the Amazon. It was observed that nut production oscillates between peaks of fall and growth, due to climatic variables and crop alternation, resulting in reflections on the price level. Brazilian exports are concentrated to the United States, Australia and European countries. With regard to imports, this occurred, especially, from Bolivia, the current market leader, even though it is among the three world producers. It was concluded that although production and market issues are usually associated exclusively with economic issues, it is observed that Brazil nuts are associated with the expansion of the agricultural frontier and a possible link with climate issues.